Effect of Acute Physical Stress on Serum Troponin-I, Inflammatory Cytokines, and Cardiovascular Parameters in Adults with Subclinical Anemia. A Clinical Investigation - Jawad Abbas, Muhammad Tariq Hamayun Khan, Amina Ijaz, Maria Mehmood, Kahkashan Perveen, Azhar Ijaz, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Subclinical anemia is a borderline hematological condition often overlooked due to the absence of overt clinical symptoms. However, it may predispose individuals to exaggerated cardiovascular and inflammatory responses when subjected to physical exertion. Understanding this physiological vulnerability is crucial, especially in physically active or at-risk populations. Objective: To evaluate the impact of acute physical stress on serum Troponin-I, inflammatory cytokines (IL-6, TNF-α, CRP), and cardiovascular parameters (heart rate, blood pressure, ECG changes) in adults with subclinical anemia compared to healthy controls. Methods: This prospective clinical study included 100 participants aged 18–40 years, recruited from the Cardiology Departments of PNS Shifa Hospital, Karachi, and Pakistan Railway Hospital, Rawalpindi. Fifty participants with subclinical anemia and fifty age- and sex-matched controls underwent a standardized treadmill stress test using the Bruce protocol. Serum samples were collected pre- and one hour post-exercise to assess Troponin-I and cytokine levels. Cardiovascular parameters and ECG changes were monitored throughout. Results: Post-exercise Troponin-I levels were significantly higher in the subclinical anemia group (0.064 ± 0.020 ng/mL) compared to controls (0.036 ± 0.012 ng/mL; p < 0.001). Inflammatory markers, including IL-6, TNF-α, and CRP, were also markedly elevated in the anemic group (p < 0.05). Cardiovascular responses such as peak heart rate and systolic blood pressure were more pronounced in anemic individuals. Transient ECG changes suggestive of myocardial ischemia were observed in 12% of the anemic group, but none in the controls. Conclusion: Subclinical anemia is associated with a heightened cardiovascular and inflammatory response to acute physical stress, indicating increased vulnerability to myocardial strain and systemic inflammation. Early recognition and management of subclinical anemia may be critical in physically active populations to prevent stress-related cardiac complications. Keywords: Subclinical anemia, Troponin-I, IL-6, Physical stress, Cardiovascular response, Inflammatory cytokines, EC